Effect of seed treatments, spacing and season of sowing on yield and quality of coriander (Coriandrum sativum L.) under rain shelter: Yield and quality of coriander under rain shelter - Anjukrishna, V U; Raj, N Mini; Anitha, P; Aneesha, A K (Journal of Spices and Aromatic Crops, 2021)
Coriander is an important herb & seed spice. The yield of coriander is influenced by the agronomic practices adopted during cultivation. This study was carried out in the Department of Plantation Crops and Spices, College of Horticulture, Vellanikkara, Kerala Agricultural University from July 2019 to March 2020 to analyse the effect of seed treatments, spacing and growing season on yield and quality of coriander leaves under rain shelter. The experiment was laid out in factorial completely randomized design (FCRD) with three replications. The study revealed that, presowing seed treatments improved the growth and yield of coriander than untreated seeds. The impact of seed treatments was conspicuous at the time of harvest on growth, yield and quality parameters. Hydropriming for 24 h was found to be the best presowing seed treatment followed by seed treatment with GA3 50 ppm for 8 h. A closer spacing of 10 x 10 cm which accommodated more plants per unit area recorded the highest biomass and herbage yield plot-1. October – December season was found to be the best for obtaining better growth and yield in leaf coriander. Hence, the study concluded that, hydropriming for 24 h or seed treatment with GA3 50 ppm for 8 h, a closer spacing of 10 x 10 cm and October – December season are the ideal combination for the best performance of variety CO-4 for leaf purpose under rain shelter in the tropical moist humid climate.